The Canadian Electronic Ensemble in the 1970s and 1980s: Panel Discussion - Montgomery, Jim; Jaeger, David; Woloshyn, Alexa; Fava, Matthew (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2021)
In this panel discussion, Alexa Woloshyn and Matthew Fava discuss the 1970s electronic and experimental music scene in Toronto, with Norma Beecroft as a leader and mentor. David Jaeger and Jim Montgomery contribute their stories, and then discuss an important international experience: the CEE’s 1985 Holland Tour. This panel discussion has been edited for clarity.